An action research in science: Providing metacognitive support to year 9 students - Wagaba, F.; Treagust, David; Chandrasegaran, Chandra; Won, Mihye (Look Academic Publishers, 2016)
© 2016 Wagaba et al. An action research study was designed to evaluate the effectiveness of providing metacognitive support to enhance Year 9 students’ metacognitive capabilities in order to better understand science concepts related to light, environmental health, ecosystems, genetics, ecology, atoms and the Periodic Table. The study was conducted over three years involving 35, 20 and 24 students in each year. The interventions included providing students with clearly stated focused outcomes about the relevant science concepts, engaging in collaborative group work, reading scientific texts and using concept mapping techniques. The data to evaluate the effectiveness of the metacognitive interventions were obtained from pre- and posttest results of the Metacognitive Support Questionnaire (MSpQ). The results showed gains in the MSpQ.